The effectiveness of chitosan as a hemostatic in dentistry in patients with antiplatelet/anticoagulant therapy: systematic review with meta-analysis - Giuseppe Minervini; Rocco Franco; Maria Maddalena Marrapodi; Marco Di Blasio; Marco Cicciù; Vincenzo Ronsivalle (BMC Oral Health, 2024)
Abstract Hemorrhage control is a crucial aspect of dental procedures, and achieving efficient hemostasis remains a key challenge. The advent of hemostatic dressings has revolutionized the field of dentistry by providing effective and convenient solutions for managing bleeding in vari-ous dental scenarios. This article aims to provide an overview of hemostatic dressings, their mechanisms of action, and their diverse applications in dentistry. We applied the following Pop-ulation, Exposure, Comparator, and Outcomes (PICO) model to assess the document eligibility. A literature search was performed on major search engines, using keywords. At the end of the search, 3 articles were selected that matched the PICO. Three items were selected after the screen-ing process, and bleeding times were analyzed between the control group and the study group. The overall effect showed a substantial and statistically significant difference with bleeding time in favour of HDD-treated patients, showing that this garrison is very useful in controlling bleed-ing for patients taking anticoagulants and antiplatelets (Mean difference − 5.61; C.I. -5.70, − 5.52); Overall, hemostatic dressings have revolutionized the management of bleeding in dentistry, offering a promising solution to achieve optimal hemostasis, improve treatment outcomes, and enhance patient care, particularly Hemcon.